Care for Dying Children and Their Families in the PICU: Promoting Clinician Education, Support, and Resilience. (August 2018) - Dryden-Palmer, Karen; Garros, Daniel; Meyer, Elaine C.; Farrell, Catherine; Parshuram, Christopher S.
Abstract : Objectives: To describe the consequences of workplace stressors on healthcare clinicians in PICU, and strategies for personal well-being, and professional effectiveness in providing high-quality end-of-life care. Data Sources: Literature review, clinical experience, and expert opinion. Study Selection: A sampling of foundational and current evidence was accessed. Data Synthesis: Narrative review and experiential reflection. Conclusions: The well-being of healthcare clinicians in the PICU influences the day-to-day quality and effectiveness of patient care, team functioning, and the retention of skilled individuals in the PICU workforce. End-of-life care, including decision making, can be complicated. Both are major stressors for PICU staff that can lead to adverse personal and professional consequences. Overresponsiveness to routine stressors may be seen in those with moral distress, and underresponsiveness may be seen in those with compassion fatigue or burnout. Ideally, all healthcare professionals in PICU can rise to the day-to-day workplace challenges—responding in an adaptive, effective manner. Strategies to proactively increase resilience and well-being include self-awareness, self-care, situational awareness, and education to increase confidence and skills for providing end-of-life care. Reactive strategies include case conferences, prebriefings in ongoing preidentified situations, debriefings, and other postevent meetings. Nurturing a culture of practice that acknowledges the emotional impacts of pediatric critical care work and celebrates the shared experiences of families and clinicians to build resilient, effective, and professionally fulfilled healthcare professionals thus enabling the provision of high-quality end-of-life care for children and their families.